Green manuring as nitrogen source for eggplant under organic cropping system - Castro, Cristina Maria de; Alves, Bruno José Rodrigues; Almeida, Dejair Lopes de; Ribeiro, Raul de Lucena Duarte (Pesquisa Agropecuaria Brasileira, 2004)
The objective of this work was to quantify biological nitrogen fixation (BNF) for green manures pre-cropped and intercropped with eggplant in an organic cropping system, the use of N from BNF by the eggplant crop, and the impact of green manuring on eggplant yield and soil N balance. Plots with sunnhemp, millet and spontaneous weeds were established before eggplant planting. After 60 days, 53% of sunnhemp N came from BNF. Since a high percentage of the spontaneous weed plots has corresponded to a legume specie, a total of 48 kg N/ha were derived from BNF. Green manure in pre-cropping was cut to planting eggplants under no-till, exception made to half of the plot under spontaneous weeds that was incorporated into the soil. The eggplant was either intercropped with sunnhemp and cowpea or cropped alone. At 52 days, the legumes were cut and left close to the eggplant. The BNF contribution to the legumes depended on the pre-cropped species and varied between 20% and 90%. Using the 15N technique, it was verified that eggplants benefited from the N of the green manure in pre-cropping or intercropping. Although without effect on eggplant yield, the BNF in the legumes was enough to compensate for the exported N in the harvested fruits.
Keywords: Solanun melongena; Crotalaria juncea; Vigna unguiculata; intercropping; biological nitrogen fixation